Organic light emitting diode display and circular polarization composite film wet process preparation method thereof
By using a retardation layer and a low-fold coating made of liquid crystal material in a semiconductor display device, the problems of image ghosting and interference fringes in the folded light path are solved, and lighter, thinner and more efficient optical devices are realized.
Patent Information
- Application Number
- CN202411936631.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing semiconductor display devices, the composite film in the rewinding light path causes image ghosting and interference with color patterns, affecting the user's viewing experience.
A retardation layer made of liquid crystal material is used to replace the retardation film prepared by stretching the traditional polymer film material, and a low-folding coating is prepared on one side of the retardation layer, and a circularly polarizing composite film is prepared through a wet process.
The thickness of the retardation film and the thickness of the overall optical device are reduced, the problem of image ghosting is reduced, and the thinness and bendability of the optical device are improved, improving the viewing experience.
Smart Images

Figure CN119360753A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor display devices, and in particular to an organic light emitting diode display and a wet process preparation method of a circularly polarized composite film thereof. Background Art
[0002] In a conventional semiconductor display device (such as an organic light emitting diode display), a return light path is used. Figure 2 As shown: light is emitted from the display screen, and most of it is reflected on the surface of the composite film (solid line). A small part of the light passes through the composite film. The light reflected by the half-reflecting mirror is reflected by the half-transparent mirror for the second time and reaches the surface of the composite film. Among the light reaching the surface of the composite film, most of the light passes through the composite film and reaches the human eye (i.e., the displayed image observed), and a small part is reflected to the display screen, and then the above propagation process is repeated again to reach the human eye (i.e., the observed stray light). Among them, the composite film is a combination of POL (absorption type linear polarizer) + RP (reflection type linear polarizer) + QWP (quarter wave plate). One side of the POL (absorption type linear polarizer) is connected to the glass lens by an adhesive. By converting the output light of the display screen into circularly polarized light, and setting a quarter wave plate on the side of the reflective linear polarizer close to the display screen, the circularly polarized light is converted into linearly polarized light, which can improve the light utilization rate of the entire optical path; but due to the interface reflection on the surface of the quarter wave plate, coupled with the interlayer reflection between the layers in the composite film and the coupling of the film thickness, the image will produce ghosting phenomenon (such as Figure 3 as shown) and interference fringes (as shown Figure 4 This will affect the user's viewing experience. Summary of the invention
[0003] The purpose of the present invention is to solve the deficiencies in the prior art and provide an organic light emitting diode display and a wet process preparation method of a circularly polarized composite film thereof.
[0004] The object of the present invention is achieved through the following technical solution: an organic light emitting diode display, comprising a circular polarizing composite film, wherein the circular polarizing composite film sequentially comprises a low-refractive coating, a phase difference layer, a reflective linear polarizer, an absorptive linear polarizer, and a lens glass; The wet process preparation method of the circularly polarized composite film comprises the following specific steps: Step 1: uniformly coating the photo-alignment solution on the carrier layer to form a photo-alignment layer; Step 2: uniformly coating the liquid crystal solution on the photo-alignment layer and aligning the photo-alignment layer to obtain a phase difference layer, wherein the dry film thickness of the phase difference layer is 0.5-5 microns; and then separating the alignment layer from the phase difference layer; Step 3: coating an adhesive on the phase difference layer, placing a reflective linear polarizer on the phase difference layer and pressing the reflective linear polarizer on the phase difference layer to obtain a reflective linear polarizer-phase difference layer composite structure; Step 4: preparing a low-refractive index coating, uniformly coating the low-refractive index coating on the side of the phase difference film away from the reflective linear polarizer, and forming a low-refractive index coating after drying and UV curing; Step 5: bonding the absorption type linear polarizer to the side of the reflection type linear polarizer away from the phase difference layer by adhesive and pressing them together to obtain a composite structure of absorption type linear polarizer-reflection type linear polarizer-phase difference layer; Step 6: Bond the side of the absorption linear polarizer away from the reflection linear polarizer to the lens glass through adhesive.
[0005] Preferably, the low-refractive index coating comprises a main filler, a photoinitiator, a leveling agent, an antioxidant, and a solvent, wherein the main filler is one or a combination of fluoropolyurethane, fluoroacrylate, silicone acrylate, and vinyl-terminated siloxane; and the solid content of the low-refractive index coating is 0-5%.
[0006] Preferably, in step 4, the low-refractive index coating is dried in a stable environment at 50-150° C. for 10-1000 seconds, and is cured by ultraviolet light in a nitrogen atmosphere, the intensity of the ultraviolet light is 500-1000 mJ, and the wavelength of the ultraviolet light is 200-400 nm.
[0007] Preferably, the dry film thickness of the low-refractive coating satisfies the following formula: λ = 4 × (1.58-n) × d / cosθ; Among them, λ is the designed central wavelength, n is the refractive index of the low-refractive coating material, d is the dry film thickness of the low-refractive coating, and θ is the refraction angle of the light after it is incident from air to the low-refractive coating.
[0008] Preferably, in step one, the components of the photoalignment solution include azo compounds, cinnamoyl compounds, coumarin compounds, polyimide compounds, and solvents. The coating dry film thickness of the photoalignment solution is 10-300nm. After the photoalignment solution is coated, it is dried at a temperature of 0-150°C for 10-1000 seconds. During the drying process, the photoalignment solution is exposed to light with an exposure intensity of 5-500mJ and an exposure wavelength of 200-600nm.
[0009] Preferably, the alignment angle of the photo-alignment layer is adjusted by adjusting the relative angle between the polarization angle of the exposure light source and the reference edge of the photo-alignment layer to achieve adjustment of the slow axis angle of the phase difference layer; the alignment angle of the photo-alignment layer is set to form an angle of 45 degrees with the transmission axis of the reflective linear polarizer.
[0010] Preferably, in step 2, after the liquid crystal solution is uniformly coated on the alignment layer, it is irradiated with ultraviolet light in a nitrogen atmosphere and dried; The liquid crystal solution is composed of lyotropic or thermotropic liquid crystal molecules with reactive functional groups dissolved in a solvent, the solution concentration is 5-50%, the drying temperature is 40-150°C, the drying time is 10-1000 seconds, the ultraviolet light irradiation intensity is 5-500mJ, and the ultraviolet light wavelength is 200-400nm; under 550nm wavelength light, the in-plane delay of the phase difference layer is 115-155nm, the transmittance of the phase difference layer is ≥90%, and the haze of the phase difference layer is ≤1%.
[0011] Preferably, the components of the adhesive include acrylate monomers, amino ester monomers, isocyanate curing agents, epoxy curing agents, free radical photoinitiators, ionic photoinitiators, silane coupling agents, and solvents, and the adhesive is cured by heating curing, light curing, or a combination thereof.
[0012] Preferably, the low-refractive coating is coated by one of micro-concave coating, slit coating and extrusion bar coating.
[0013] A circular polarizing composite film comprises a low-refractive coating, a phase difference layer, a reflective linear polarizer, an absorbing linear polarizer and lens glass in sequence.
[0014] The beneficial effects of the present invention are: 1. The present invention replaces the traditional phase difference film prepared by stretching a polymer film material with a phase difference layer made of liquid crystal material. The phase difference layer made of liquid crystal material can be prepared by coating a liquid crystal solution, which can greatly reduce the thickness of the phase difference film, thereby reducing the phase difference between the upper and lower surfaces of the phase difference film, thereby alleviating the image ghosting problem; and thanks to the reduction in the thickness of the phase difference film, the overall thickness of the circularly polarized composite film can be significantly reduced, making the entire optical device thinner and lighter, and the bendability is also significantly improved.
[0015] 2. In the present invention, a phase difference layer is prepared by optical alignment of a liquid crystal solution. The phase difference layer can be oriented obliquely during the preparation process. Oblique alignment means that the liquid crystal molecules are not arranged completely parallel to the substrate surface, but have a certain tilt angle. This alignment method can give the phase difference layer unique optical properties, such as wide viewing angle, high transparency, etc. The flexibility of oblique alignment makes it possible to adjust the alignment angle according to different application needs to meet specific optical requirements. Since the alignment angle is relatively flexible, it can adapt to the roll-to-roll production process. The roll-to-roll production process is efficient and flexible, which can effectively improve production efficiency, and has a high cutting utilization rate, reducing material waste.
[0016] 3. The present invention provides a low-refractive coating on one side of the phase difference film. After the low-refractive coating is added, when light is incident from the air layer through the low-refractive coating to the surface of the phase difference layer, it will be reflected at the side where the low-refractive coating contacts the air and the side where the low-refractive coating contacts the phase difference layer. When the optical path difference between the two reflected light beams is (2N+1)π (N is a natural number), they are superimposed and destructive. The present invention controls the thickness and refractive index of the low-refractive coating and utilizes the superposition and destructive effect of light to reduce or eliminate the surface reflection of the phase difference layer, thereby reducing or eliminating the problems of ghosting and interference color fringes.
[0017] 4. The present invention prepares the phase difference layer by coating the liquid crystal solution on the photo-alignment layer. The entire preparation process is non-contact production, and the appearance quality is better. However, the traditional polymer film stretching preparation process may cause defects on the film surface, such as wrinkles and scratches, due to contact and tension during the stretching process, thereby affecting the appearance quality of the product, and the appearance quality is not as good as the present invention.
[0018] 5. In the present invention, a low refractive layer is prepared on one side of the phase difference layer by a wet process (by coating with a low refractive coating). The equipment and implementation method required for the wet process are relatively simple, the process cost is low, the operation is simple, the process controllability is high, and it is convenient for large-scale production. The low refractive coating can dissolve a variety of polymers or compounds of different properties through a solvent, so that the desired film can be easily prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic structural diagram of the circularly polarized composite film of the present invention.
[0020] Figure 2 A schematic diagram of a return light path in a conventional semiconductor display device.
[0021] Figure 3 Schematic diagram of ghosting of an image.
[0022] Figure 4 Schematic diagram of the interference pattern generated for the image.
[0023] Figure 5 The present invention provides a light reflectivity comparison curve diagram of a circular polarizer with a low-refractive index coating added thereto and a conventional circular polarizer. DETAILED DESCRIPTION
[0024] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0025] Those skilled in the art should understand that, in the disclosure of the present invention, the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship, are based on the orientation or position relationship shown in the drawings, which are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation. Therefore, the above terms should not be understood as limiting the present invention.
[0026] It is to be understood that the term "one" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element may be one, while in another embodiment, the number of the element may be multiple, and the term "one" should not be understood as a limitation on the quantity.
[0027] like Figure 1 As shown, an organic light emitting diode display comprises a circular polarizing composite film, wherein the circular polarizing composite film comprises a low-refractive coating, a phase difference layer, a reflective linear polarizer, an absorbing linear polarizer, and a lens glass in sequence; The wet process preparation method of the circularly polarized composite film comprises the following specific steps: Step 1: uniformly coating the photo-alignment solution on the carrier layer to form a photo-alignment layer; Step 2: uniformly coating the liquid crystal solution on the photo-alignment layer and aligning the photo-alignment layer to obtain a phase difference layer, wherein the dry film thickness of the phase difference layer is 0.5-5 microns; and then separating the alignment layer from the phase difference layer; Step 3: coating an adhesive on the phase difference layer, placing a reflective linear polarizer on the phase difference layer and pressing the reflective linear polarizer on the phase difference layer to obtain a reflective linear polarizer-phase difference layer composite structure; Step 4: preparing a low-refractive index coating, uniformly coating the low-refractive index coating on the side of the phase difference film away from the reflective linear polarizer, and forming a low-refractive index coating after drying and UV curing; Step 5: bonding the absorption type linear polarizer to the side of the reflection type linear polarizer away from the phase difference layer by adhesive and pressing them together to obtain a composite structure of absorption type linear polarizer-reflection type linear polarizer-phase difference layer; Step 6: Bond the side of the absorption linear polarizer away from the reflection linear polarizer to the lens glass through adhesive.
[0028] In the present invention, a phase difference layer made of liquid crystal material replaces the phase difference film prepared by stretching a traditional polymer film material. The phase difference layer made of liquid crystal material can be prepared by coating a liquid crystal solution, which can greatly reduce the thickness of the phase difference film, and the thickness can reach 0.5-5 microns. The thickness of the traditional phase difference film prepared by stretching a polymer film material is generally greater than 50 microns. Since the thickness of the phase difference film in the present invention is greatly reduced, the phase difference between the upper and lower surfaces of the phase difference film is reduced, thereby alleviating the image ghosting problem; and thanks to the reduction in the thickness of the phase difference film, the overall thickness of the circularly polarized composite film can be significantly reduced, making the entire optical device thinner and lighter, and the bendability is also significantly improved.
[0029] The present invention prepares the phase difference layer by photo-alignment of the liquid crystal solution. The phase difference layer can be obliquely aligned during the preparation process. Oblique alignment means that the liquid crystal molecules are not arranged completely parallel to the substrate surface, but have a certain tilt angle. This alignment method can give the phase difference layer unique optical properties, such as wide viewing angle, high transparency, etc. The flexibility of oblique alignment allows the alignment angle to be adjusted according to different application requirements to meet specific optical requirements; since the alignment angle is relatively flexible, it can be adapted to the roll-to-roll production process. The roll-to-roll production process has the characteristics of high efficiency and flexibility, which can effectively improve production efficiency, and has a high cutting utilization rate and reduces material waste. In addition, the present invention prepares the phase difference layer by coating the liquid crystal solution on the photo-alignment layer. The entire preparation process is non-contact production, and the appearance quality is better. However, the traditional polymer film stretching preparation process may cause defects on the surface of the film material, such as wrinkles, scratches, etc., due to contact and tension during the stretching process, thereby affecting the appearance quality of the product, and the appearance quality is not as good as the present invention.
[0030] The present invention adopts a roll-to-roll production process with higher production efficiency. In order to meet the production rhythm of the roll-to-roll production process, the low-refractive index coating is prepared by uniformly coating the low-refractive index coating on the photo-alignment layer (i.e., a wet process). The wet process is carried out under normal pressure and can be operated in an open environment, thus meeting the requirements of roll-to-roll continuous production and having higher production efficiency.
[0031] When light is incident from the air layer to the surface of the material, the light is reflected due to the difference in refractive index of the materials on both sides of the incident interface. When the thickness between the two interfaces reaches the micrometer level or below, the reflected light from the two different interfaces interferes, thereby generating ghost images and interference fringes. The refractive index of the low-refractive coating is the material layer between the phase difference layer and the air layer. After adding the low-refractive coating, when the light is incident from the air layer through the low-refractive coating to the surface of the phase difference layer, it will be reflected on the side where the low-refractive coating contacts the air and the side where the low-refractive coating contacts the phase difference layer. When the optical path difference of the two beams of reflected light is (2N+1)π (N is a natural number), they are superimposed and destructive. When the optical path difference of the two beams of light is 2Nπ (N is a natural number), they are superimposed and additive. The present invention controls the thickness and refractive index of the low-refractive coating, and utilizes the superimposed and destructive effect of light to reduce or eliminate the surface reflection of the phase difference layer, thereby reducing or eliminating the ghost image and interference color fringes.
[0032] Among them, in step three, the absorption type linear polarizer and the phase difference layer are pressed together by a composite roller; on the one hand, the composite roller can apply pressure to the absorption type linear polarizer and the phase difference layer to ensure effective combination between the two, and on the other hand, the thickness of the adhesive between the absorption type linear polarizer and the phase difference layer can be controlled by the composite roller, thereby reducing the interference lines generated in the return light path.
[0033] Similarly, in step five, the absorptive linear polarizer and the reflective linear polarizer are pressed together by a composite roller; on the one hand, the composite roller can apply pressure to the absorptive linear polarizer and the reflective linear polarizer to ensure effective combination between the two, and on the other hand, the composite roller can control the thickness of the adhesive between the absorptive linear polarizer and the reflective linear polarizer, thereby reducing the interference patterns generated in the return light path.
[0034] In step 1, the components of the photo-alignment solution include azo compounds, cinnamoyl compounds, coumarin compounds, polyimide compounds, and solvents. The thickness of the dry film of the photo-alignment solution is 10-300 nm. After the photo-alignment solution is coated, it is dried at a temperature of 0-150° C. for 10-1000 seconds. During the drying process, the photo-alignment solution is exposed to light with an exposure intensity of 5-500 mJ and an exposure wavelength of 200-600 nm. The concentration of the photo-alignment solution is 1-5%.
[0035] The alignment angle of the photo-alignment layer is adjusted by adjusting the relative angle between the polarization angle of the exposure light source and the reference edge of the photo-alignment layer to adjust the slow axis angle of the phase difference layer; the alignment angle of the photo-alignment layer is set to form a 45-degree angle with the transmission axis of the reflective linear polarizer.
[0036] The alignment angle of the photo-alignment layer determines the arrangement direction of the liquid crystal molecules, and thus determines the slow axis angle of the phase difference film. By setting the alignment angle to be 45 degrees with the light transmission axis of the reflective linear polarizer, roll-to-roll lamination can be facilitated, the process complexity can be simplified, and the operation efficiency and material utilization can be improved.
[0037] In step 2, after the liquid crystal solution is uniformly coated on the alignment layer, it is irradiated with ultraviolet light in a nitrogen atmosphere and dried. The liquid crystal solution is composed of lyotropic or thermotropic liquid crystal molecules with reactive functional groups dissolved in a solvent, the solution concentration is 5-50%, the drying temperature is 40-150°C, the drying time is 10-1000 seconds, the ultraviolet light irradiation intensity is 5-500mJ, and the ultraviolet light wavelength is 200-400nm; the in-plane delay of the phase difference layer under 550nm wavelength light is 115-155nm, the transmittance of the phase difference layer is ≥90%, and the haze of the phase difference layer is ≤1%.
[0038] In this embodiment, the liquid crystal solution is composed of lyotropic or thermotropic liquid crystal molecules with reactive functional groups of carbon-carbon double bonds dissolved in a solvent, and the concentration of the liquid crystal solution is 5-50%. In the present invention, the transmittance of the phase difference layer is 90%, and the haze of the phase difference layer is less than 1%, which can effectively reduce the loss of light passing through the phase difference layer, and the user can obtain a higher quality image.
[0039] The coating method of the liquid crystal solution and the photo-alignment solution is one of micro-concave coating, slit coating and extrusion doctor bar coating.
[0040] In step 4, the low-refractive index coating includes a main filler, a photoinitiator, a leveling agent, an antioxidant, and a solvent. The main filler is one or a combination of fluoropolyurethane, fluoroacrylate, silicone acrylate, and vinyl-terminated siloxane; the solid content of the low-refractive index coating is 0-5%.
[0041] The low-refractive coating is dried for 10-1000 seconds in a stable environment at 50-150°C, and is cured by ultraviolet light in a nitrogen atmosphere, with an intensity of 500-1000mJ and a wavelength of 200-400nm.
[0042] Among them, the coating method of the low-refractive coating adopts one of micro-concave coating, slit coating, and extrusion doctor bar coating.
[0043] In the present invention, a low refractive layer is prepared on one side of the phase difference layer by a wet process (by coating with a low refractive coating). The equipment and implementation method required for the wet process are relatively simple, the process cost is low, the operation is simple, the process controllability is high, and it is convenient for large-scale production. The low refractive coating can dissolve a variety of polymers or compounds of different properties through a solvent, so that the desired film can be easily prepared.
[0044] The refractive index of the low-refractive coating is between that of the phase difference layer and air. In this embodiment, the refractive index of the phase difference layer is about 1.6, and the refractive index of the low-refractive coating is 1.3-1.48.
[0045] The dry film thickness of the low-refractive coating satisfies the following formula: λ = 4 × (1.58-n) × d / cosθ; Wherein, λ is the designed center wavelength. In the embodiment, the designed center wavelength λ is 550 nm. n is the refractive index of the low-refractive coating material, d is the dry film thickness of the low-refractive coating, and θ is the refraction angle of light after it is incident from air to the low-refractive coating.
[0046] The adhesive used in the present invention comprises components of acrylate monomers, amino ester monomers, isocyanate curing agents, epoxy curing agents, free radical photoinitiators, ionic photoinitiators, silane coupling agents, and solvents. The adhesive is cured by heating or light curing, or a combination thereof.
[0047] A circularly polarized composite film is prepared by the preparation method described above.
[0048] like Figure 1 As shown, the prepared circularly polarized composite film includes, from top to bottom, a low-refractive coating, a phase difference layer, a reflective linear polarizer, an adhesive, an absorptive linear polarizer, an adhesive, and a glass lens.
[0049] like Figure 5 As shown, Figure 5 The graph is a comparison of the light reflectance of the circular polarizer with the low-refractive index coating added in the present invention and the traditional circular polarizer, wherein the horizontal axis of the graph is the wavelength of light in nanometers, and the vertical axis is the light reflectance. The blue curve is the reflectance of the circular polarizer without the low-refractive index coating to light of different wavelengths, and the orange curve is the reflectance of the circular polarizer with the low-refractive index coating added in the present invention to light of different wavelengths. Figure 5 It can be seen that by adding a low-refractive coating, the reflection of light of different wavelengths is effectively reduced.
[0050] The following are several different preparation examples of circularly polarized composite films: Example 1:
[0051] Example 2:
[0052] Example 3:
[0053] Example 4:
[0054] Example 5:
[0055] By comparing the above examples, it can be seen that by changing the phase difference layer to a liquid crystal material and adding a low-reflection layer, the problems of ghosting and interference color fringes are effectively solved.
[0056] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.
Claims
1. An organic light emitting diode display, characterized in that: It includes a circular polarizing composite film, which includes a low-refractive coating, a phase difference layer, a reflective linear polarizer, an absorbing linear polarizer, and lens glass in sequence; The wet process preparation method of the circularly polarized composite film comprises the following specific steps: Step 1: uniformly coating the photo-alignment solution on the carrier layer to form a photo-alignment layer; Step 2: uniformly coating the liquid crystal solution on the photo-alignment layer and aligning the photo-alignment layer to obtain a phase difference layer, wherein the dry film thickness of the phase difference layer is 0.5-5 microns; and then separating the alignment layer from the phase difference layer; Step 3: coating an adhesive on the phase difference layer, placing a reflective linear polarizer on the phase difference layer and pressing the reflective linear polarizer on the phase difference layer to obtain a reflective linear polarizer-phase difference layer composite structure; Step 4: preparing a low-refractive index coating, uniformly coating the low-refractive index coating on the side of the phase difference film away from the reflective linear polarizer, and forming a low-refractive index coating after drying and UV curing; Step 5: bonding the absorption type linear polarizer to the side of the reflection type linear polarizer away from the phase difference layer by adhesive and pressing them together to obtain a composite structure of absorption type linear polarizer-reflection type linear polarizer-phase difference layer; Step 6: Bond the side of the absorption linear polarizer away from the reflection linear polarizer to the lens glass through adhesive.
2. The organic light emitting diode display according to claim 1, characterized in that: The low-refractive index coating comprises a main filler, a photoinitiator, a leveling agent, an antioxidant, and a solvent. The main filler is one or a combination of fluoropolyurethane, fluoroacrylate, silicone acrylate, and vinyl-terminated siloxane. The solid content of the low-refractive index coating is 0-5%.
3. The organic light emitting diode display according to claim 1, characterized in that: In step 4, the low-refractive coating is dried in a stable environment at 50-150° C. for 10-1000 seconds, and is cured by ultraviolet light in a nitrogen atmosphere, with an intensity of 500-1000 mJ and a wavelength of 200-400 nm.
4. The organic light emitting diode display according to claim 1, characterized in that: The dry film thickness of the low-refractive coating satisfies the following formula: λ = 4 × (1.58-n) × d / cosθ; Among them, λ is the designed central wavelength, n is the refractive index of the low-refractive coating material, d is the dry film thickness of the low-refractive coating, and θ is the refraction angle of the light after it is incident from air to the low-refractive coating.
5. The organic light emitting diode display according to claim 1, characterized in that: In step one, the components of the photoalignment solution include azo compounds, cinnamoyl compounds, coumarin compounds, polyimide compounds, and solvents. The coating dry film thickness of the photoalignment solution is 10-300nm. After the photoalignment solution is coated, it is dried at a temperature of 0-150°C for 10-1000 seconds. During the drying process, the photoalignment solution is exposed to light with an exposure intensity of 5-500mJ and an exposure wavelength of 200-600nm.
6. The organic light emitting diode display according to claim 5, characterized in that: The alignment angle of the photo-alignment layer is adjusted by adjusting the relative angle between the polarization angle of the exposure light source and the reference edge of the photo-alignment layer to adjust the slow axis angle of the phase difference layer; the alignment angle of the photo-alignment layer is set to form a 45-degree angle with the transmission axis of the reflective linear polarizer.
7. The organic light emitting diode display according to claim 1, characterized in that: In step 2, after the liquid crystal solution is uniformly coated on the alignment layer, it is irradiated with ultraviolet light in a nitrogen atmosphere and dried; The liquid crystal solution is composed of lyotropic or thermotropic liquid crystal molecules with reactive functional groups dissolved in a solvent, the solution concentration is 5-50%, the drying temperature is 40-150°C, the drying time is 10-1000 seconds, the ultraviolet light irradiation intensity is 5-500mJ, and the ultraviolet light wavelength is 200-400nm; under 550nm wavelength light, the in-plane delay of the phase difference layer is 115-155nm, the transmittance of the phase difference layer is ≥90%, and the haze of the phase difference layer is ≤1%.
8. The organic light emitting diode display according to claim 1, characterized in that: The components of the adhesive include acrylate monomers, amino ester monomers, isocyanate curing agents, epoxy curing agents, free radical photoinitiators, ionic photoinitiators, silane coupling agents, and solvents. The adhesive is cured by heating or light curing, or a combination thereof.
9. The organic light emitting diode display according to claim 1, characterized in that: The coating method of the low-refractive coating is one of micro-concave coating, slit coating, and extrusion doctor bar coating.
10. A circularly polarized composite film, characterized in that: It includes a low-refractive coating, a phase difference layer, a reflective linear polarizer, an absorbing linear polarizer, and lens glass in sequence.
Citation Information
Patent Citations
Antireflective optical protecting film and preparation method
CN104597530A
Light splitting assembly and augmented reality display device
CN116430504A
Optical plate capable of repeatedly utilizing optical alignment layer as well as preparation process and application of optical plate
CN118276359A
Double anti-UV antireflection film and preparation method thereof
CN119087558A
Circular polarizer and display device
CN220526028U